Think-Aloud Protocols in process studies revisited: Suggestions for veridicality - Sugirin, Sugirin; Jamilah, Jamilah; Priyana, Joko; Permatasari, Indah (Universitas Islam Sultan Agung, 2024)
Thinking-Aloud or Think-Aloud Protocols have been used to study thinking processes in varied fields such as psychology, business, sports, industry, and education. Recently, studies have tried to see its application in teaching in both offline and online modes. Despite its success, as demonstrated by these studies, controversies concerning the believability of thinking aloud and the process of reactivity have been raised. However, no explicit solution has been provided. In response to the issues, this paper critically reviewed examples of think-aloud protocols using Bowles’s guide to TAP (2008). The results show that (1) problems of the reactivity process stem from the nature of the tasks given, and (2) to minimize the problems of reactivity, the TAP data collection procedure should move from the least to the most intervention of the researcher.